S1PR3 deficiency alleviates radiation‐induced pulmonary fibrosis through the regulation of epithelial–mesenchymal transition by targeting miR‐495‐3p. Issue 3 (5th September 2019) - Gong, Linjing; Wu, Xu; Li, Xinyi; Ni, Xiaoying; Gu, Wenyu; Wang, Xinyuan; Ji, Haiying; Hu, Lijuan; Zhu, Lei
Abstract: Radiation‐induced pulmonary fibrosis (RIPF) is a life‐threatening complication of thoracic radiotherapy, which contributes to continued deterioration in pulmonary function. Sphingosine‐1 phosphate receptor 3 ( S1PR3 ) has been identified as a crucial molecule in fibrosis. Accumulating evidence indicated that the inhibition of the S1PRs ameliorates fibrogenesis. Thus, this study aims to explore whether S1PR3 participates in RIPF and elucidates the molecular mechanisms underlying S1PR3‐modulated epithelial–mesenchymal transition (EMT) in transforming growth factor‐β1‐induced pulmonary epithelia. A recombinant adeno‐associated viral‐mediated S1PR3 (AAV‐S1PR3) gene therapy analyzed the effect of S1PR3 gene deficiency on the altered histology structure and molecular mechanisms in the lung of mice with whole‐lung irradiation. Compared with the AAV‐negative control mice, AAV‐mediated S1PR3 knockdown in the lung of mice attenuated pulmonary fibrosis induced by the radiation, as indicated by the alleviation of collagen accumulation, lessened histopathological alterations, and the suppression of inflammatory cells infiltration. S1PR3 deficiency reversed the RIPF concomitantly with abrogated EMT‐related protein (α‐smooth muscle actin). Consistently, S1PR3‐deficient pulmonary epithelia inhibited the EMT process changes and fibrosis formation. Furthermore, S1PR3 was designated as one of the target genes for microRNA‐495‐3p (miR‐495‐3p). The inhibition of miR‐495‐3p promoted the expression of S1PR3 in pulmonary epithelia, whereas the overexpression of miR‐495‐3p inhibited the S1PR3/SMAD2/3 pathway and suppressed the EMT process. Collectively, miR‐495‐3p might be a negative regulator of the EMT process in fibrosis formation by inhibiting the targeted S1PR3 gene. These results established a link between the S1PR3 gene, the EMT process, and the fibrosis, suggesting the pharmacological blockage of S1PR3 as a potential therapeutic strategy for RIPF. Abstract : Radiation and transforming growth factor‐β1 (TGF‐β1) promoted the translation of S1PR3, thus upregulating the expression of Smad2/3 proteins and potentiating the epithelial–mesenchymal transition process, then the formation of pulmonary fibrosis. However, microRNA‐495‐3p inhibited those signaling pathways by its target gene S1PR3.